(untitled) (Research, Society and Development, 2020)
Many species of medicinal plants have been used as a therapeutic alternative in the treatment of diseases around the world, as well as promoting advances in the production of herbal medicines. However, this use is often done indiscriminately and leads to serious consequences in the body of those who use them. Therefore, studies on the toxic, cytotoxic, and genotoxic potentials of medicinal plant species are necessary for their safe use. Cenostigma gardnerianum Tul, popularly known as Caneleiro or Canela-de-velho, is widely used by the population for its anti-inflammatory, antispassmolytic, antitussive, antifungal properties, among others. The aim of this research was to study and analyze a possible toxicity, cytotoxicity, and genotoxicity of the ethanolic extract from the bark of the stem of Cenostigma gardnerianum Tul. by means of the Allium cepa in vivo bioassay. The extract was divided into four concentrations, divided into groups A, B, C and D, respectively: 0.5mg/ml, 1.0mg/ml, 2.0mg/ml and 5.0mg/ml, in addition to the Negative Control (dechlorinated water), Positive Control (dimethyl sulfoxide) and Blank control (distilled water). The roots were measured for toxicity evaluation, the Mitotic Index (MI) was calculated for cytotoxicity research, and finally micronuclei count was performed to study the genotoxicity of each extract concentration. The low growth of the meristems indicated the presence of toxicity; the mitotic indices found were statistically lower than in the negative control, revealing cytotoxicity; and the high micronucleus count showed the presence of genotoxicity. From the results obtained, it was concluded that the ethanolic extract of the Caneleiro bark presents toxic, cytotoxic, and genotoxic activity, with statistically significant values for concentrations starting from 2mg/ml.